The Analysis of Factors Influencing the Reduction of Abnormal Behaviors in the Workplace Based on Meta-Synthesis Technique - Shahpar Zakipour; Behzad Farrokh Sersht; Mohammad Javad Taghipourian; Hasan Ali Aghajani (Tehran University of Medical Sciences, 2020)
Background and Aim: In recent decades, increasing productivity and reducing losses by improving abnormal behaviors in the workplace have attracted the attention of organizational behavior experts, especially health researchers. The purpose of the present research is to study the factors influencing the reduction of abnormal behaviors in health workplace. Materials and Methods: By using meta-synthesis technique, the findings of the related internal and external studies were systematically analyzed using Sandelowski and Barroso seven-step method. The identified codes were classified, analyzed and interpreted by MAXQDA10. Kappa method and SPSS were used to measure reliability and quality control. The calculated kappa coefficient was 0.893, which indicated a good consistency. Results: From 435 articles investigated in this field, 46 articles were selected, based on which 68 factors were identified. These factors were classified into 3 main categories and 11 pivotal codes. The influential factors identified in this study include individual factors(psychological, demographic, religious, and contextual), group factors(communication, appropriate reward system, and deterrent behaviors) and organizational factors(organizational space, organizational measures, organizational emotions, and job position perception). Conclusion: The results of this study show that individual factors are the most important ones affecting the reduction of abnormal behaviors. Therefore, the findings of this study emphasize psychological, demographic, religious, and contextual factors in planning and managers' interventions to increase productivity in health workplace.